2010
DOI: 10.5116/ijme.4bda.ca2a
|View full text |Cite
|
Sign up to set email alerts
|

Developing medical professionalism in future doctors: a systematic review

Abstract: Objectives: There are currently no guidelines on the most effective ways of supporting medical students to develop high standards of medical professionalism. The aim of this review is to summarise the evidence currently available on methods used by medical schools to promote medical professionalism.Methods: We performed a systematic search of electronic databases (Medline, PsychInfo, British Education Index, Educational Resources Information Centre, Sociological Abstracts and Topics in Medical Education) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
0
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(154 citation statements)
references
References 135 publications
2
135
0
17
Order By: Relevance
“…Passi et al identified three characteristics of good role models, i.e., clinical competence, teaching skills, and personal qualities. 30 Almost certainly, trainees recognized as excellent role models those physicians who, in addition to providing good clinical care, took the time to facilitate feedback and made a conscious effort to articulate what they were modelling. This is a demanding expectation, and there are issues with consistently modelling such behaviours.…”
Section: Strategies For Teaching and Modelling Professional Behaviourmentioning
confidence: 99%
“…Passi et al identified three characteristics of good role models, i.e., clinical competence, teaching skills, and personal qualities. 30 Almost certainly, trainees recognized as excellent role models those physicians who, in addition to providing good clinical care, took the time to facilitate feedback and made a conscious effort to articulate what they were modelling. This is a demanding expectation, and there are issues with consistently modelling such behaviours.…”
Section: Strategies For Teaching and Modelling Professional Behaviourmentioning
confidence: 99%
“…When the data were evaluated to better determine the dynamics of this decline, we observed the greatest reduction in the students' performance during the intermediate cycle (i.e., between the 3rd and 4th school years). These data indicate the need to revise the curriculum and extend the teaching of professional attitudes to the clinical phase of the curriculum, as several authors have suggested 8,[10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…Teaching and evaluating students' professional development remains one of the most difficult core content areas in undergraduate medical education. The difficulty of identifying a valid and reliable instrument to measure attitudinal performance is reflected in the large number of measures aimed at assessing constructs related to medical professionalism that have been published to date [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…As professionalism is considered an important part of a health worker's contract with society, every individual has to continue improving by constant personal development training and continuing exposure of themselves to different experiences (Kirk, 2007). There are voices calling that the selection of health workers or health workers to be, has to start even on the admission process to the institutions (Passi et al, 2010;Waheet et al, 2011;Scotish Government, 2012). Professionalism of the individuals who are involved in health care is necessary to be assessed by using a multitude of methods (Salvatori, 1996;Redfern et al, 2002).…”
Section: Discussionmentioning
confidence: 99%